2017
DOI: 10.1007/s10461-017-1937-9
|View full text |Cite
|
Sign up to set email alerts
|

Couple Relationship Functioning as a Source or Mitigator of HIV Risk: Associations Between Relationship Quality and Sexual Risk Behavior in Peri-urban Uganda

Abstract: Despite evidence that a greater focus on couples could strengthen HIV prevention efforts, little health-related research has explored relationship functioning and relationship quality among couples in Africa. Using data from 162 couples (324 individuals) resident in a peri-urban Ugandan community, we assessed actor and partner effects of sexual risk behaviors on relationship quality, using psychometric measures of dyadic adjustment, sexual satisfaction, commitment, intimacy, and communication. For women and me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 33 publications
(37 reference statements)
0
17
0
Order By: Relevance
“…Because relationship quality has received even less attention in the African context, our intention was to explore associations with individual constructs of relationship quality and allow for nuanced patterns to emerge. Further, as discussed previously, the one study that has examined alcohol use and relationship quality in Africa (Ruark et al, 2017) also used separate models for each relationship quality domain, and indeed found both gender differences in the association between relationship quality and alcohol use before sex, as well as different findings for different domains of relationship quality.…”
Section: Methodsmentioning
confidence: 86%
See 3 more Smart Citations
“…Because relationship quality has received even less attention in the African context, our intention was to explore associations with individual constructs of relationship quality and allow for nuanced patterns to emerge. Further, as discussed previously, the one study that has examined alcohol use and relationship quality in Africa (Ruark et al, 2017) also used separate models for each relationship quality domain, and indeed found both gender differences in the association between relationship quality and alcohol use before sex, as well as different findings for different domains of relationship quality.…”
Section: Methodsmentioning
confidence: 86%
“…There are some experimental data from alcohol administration studies with couples in the U.S. (Frankenstein, Hay, & Nathan, 1985; Smith, et al, 1975) and observational, experience sampling studies (e.g., aan het Rot, Russell, Moskowitz, & Young, 2008) in support of the intrepretation that alcohol use facilitaties positive affective expression. It is also possible that the measure of intimacy we used was more an approximation of caregiving (“I get so close to my partner I find it hard to separate from him”; “I think in terms of we/us instead of I/me”), rather than emotional intimacy as assessed by Ruark et al (2017) (“I receive/give considerable emotional support to my partner”; “I feel that I really understand my partner”), who found alcohol use before sex to be unrelated to women’s feelings of intimacy.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Research among South African couples enrolled in an HIV prevention trial found that shared power was a stronger correlate of relationship quality (e.g., trust, intimacy) than women's own power or men's beliefs about equitable gender norms (Conroy et al 2016). Relationship quality is also associated with positive health behaviours such as condom use and medication adherence (Ruark, Kajubi et al 2017;Conroy, Ruark, and Darbes 2018). Connell's (1987) theory of gender and power provides the theoretical basis for the vulnerability paradigm and argues that three social structures characterise the relationship between men and women: (1) the sexual division of labour; (2) the sexual division of power; and (3) cathexis, or social norms and affective attachments around femininity and masculinity.…”
Section: Introductionmentioning
confidence: 99%